Supercritical fluid extraction of sterols from Eichhornia crassipes biomass using pure and modified carbon dioxide. Enhancement of stigmasterol yield and extract concentration - Martins, Pedro F.
The supercritical extraction of stalks and leaves of Eichhornia crassipes was carried out using pure and modified carbon dioxide. Preliminary results evidenced that the influence of temperature is weaker than pressure and ethanol content, and thus a design of experiments was performed in the ranges of 200-300 bar and 0.0-5.0 wt.% ethanol. The optima conditions for total extraction yield (eta(Total)) were 250-300 bar and 5.0 wt.% of cosolvent, while for sterols yield (eta(TotalSterol)) they were 300 bar and 2.5 wt.%. The latter conditions were also the most favorable to maximize the concentration of total sterols in the extracts (C-TotalSterol), particularly stigmasterol (C-stigm), the most abundant one. For the referred optima, eta(Total) = 1.25 wt.%, eta(TotalSterol) =0.35 wt.%, C-TotalSterol =38.26 wt.%, and C-stigm =26.35 wt. %. This study showed also that the individual trends of stigmasterol and cholesterol were closer to the total sterols fraction behavior than beta-sitosterol did, and also that the sterols concentration were higher in the first 2 h of extraction. In the whole, this article provides a pertinent contribution for the valorization of E. crassipes biomass through the production of natural extracts with high contents of sterols, especially stigmasterol, mainly if one takes into account it is classified as the most problematic invasive plant worldwide. (C) 2015 Elsevier B.V. All rights reserved.